Leg extensions power of elite swimmers - Miyashita, M.; Takahashi, S.; Troup, J. P.; Wakayoshi, K. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The maximal leg extension power of elite swimmers was determined using an electric measuring device. There was a positive relationship between starting performance and leg extension power. A large sex difference was found in the maximal power event though expressed relative to body weight. Age group swimmers were inferior to the national swimmers in absolute power, but when compared in values relative to body weight, the difference decreased, especially in female swimmers. No racial difference existed in the maximal power between American swimmers and Japanese swimmers.